Turning the game around for conservation: using traditional hunting knowledge to improve the capture efficiency of Amazon lowland pacas. Issue 1 (1st January 2016) - Bizri, Hani Rocha El; Araújo, Luiz Washington da Silva; Araújo, Wigson da Silva; Maranhão, Louise; Valsecchi, João
Abstract : The lowland paca Cuniculus paca is a large rodent and is one of the most hunted mammal species in the Neotropics. Conservation strategies for the lowland paca that depend on data from live captures have been hampered due to the elusive behavior of the species. Here, we introduce a scientifically standardized version of a traditional method used by hunters in the Amazon to capture pacas and compare its cost‐effectiveness with conventional scientific methods. First, we used each of these methods at 11 sites in the Brazilian Amazon. The hunting technique captured 12 pacas, whereas the conventional methods captured none, and the hunting technique proved to be as inexpensive as the least‐costly conventional method. Second, we analyzed the cost‐effectiveness of the methods by comparing the results obtained in the field with data from previous paca studies. The hunting method was four‐fold more efficient than the study with the highest paca capture rates achieved to date. This study shows that the use of a hunting technique to capture paca is an efficient and safe procedure that may be applied at different sites in the Amazon and represents an example of how traditional knowledge can be used in partnership with science to enhance the development of successful conservation efforts.